PERSEPSI SISWA TERHADAP PENJASORKES DI SMK DAN SMA SE - KECAMATAN MEMPAWAH TIMUR KABUPATEN PONTIANAK - Yulianto, Awang; Kaswari, Kaswari; Supriatna, Eka (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this study was how is student?s perception of PENJASORKES in Vocational High Schools (SMKs) and Senior High Schools (SMAs) of the entire areas-coverage of East Mempawah subdistrict in Pontianak Regency. The purpose of this study was to determine students' perceptions of PENJASORKES in SMK and SMA of East Mempawah in Pontianak Regency. This descriptive study used survey technique by distributing questionnaires to collect study data. The study subjects consisted of 76 students. The analysis results of the data obtained from the questionnaires can be concluded: The perceptions of students in SMK and SMA in Eastern Mempawah subdistrict on PENJASORKES consist of both internal and external factors that are elaborated into sub-factors as follows: Internal factor comprises Physiological, Atmosphere, Experience and memory, unidirectional needs, Attention, and Interest. While, external factor covers Size and placement of objects, motion or movement, intensity of stimulus, color of object, uniqueness of stimulus. Thus, the results of this study indicate that physiology and atmosphere are the most dominant internal factors with a percentage of 17.49%. While the external factors consist of size and placement of objects, with a percentage of 25.79%. Keywords: Perception, PENJASORKES, Senior High Schools